L- Arginine and Nitric Oxide Levels Among Children with Sickle Cell Disease Presented With Vaso-Occlusive Crisis in Federal Teaching Hospital Gombe, North Eastern Nigeria. - Abubakar, S.; Erhabor, O.; Ibrahim, K. K.; Waziri, G.; Ibrahim, A. B.; Saleh Yuguda; Girei, A.; Adamu, S.; Isyaku, S.; Tilako B. H. (British Journal of Healthcare and Medical Research, 2023)
Aim: The Aim of This Study Is To Evaluate The Level Of L- Arginine And Nitric Oxide Levels Among Children With Sickle Cell Disease presented with vaso-occlusive crisis in pediatric department, Federal Teaching Hospital Gombe, North Eastern Nigeria. Methology: The area selected for this study was Federal Teaching Hospital (FTH), Gombe, Nigeria. Gombe State is located in the North- estern part of Nigeria. This study included 60 children aged 1-14 years with a confirmed HbSS electrophoretic pattern presented to the sickle cell clinic unit of Federal Teaching Hospital Gombe, Gombe State. About 5 millilitres of blood sample was collected from each subject aseptically using the venepuncture technique. The blood was collected into tubes containing dipotassium ethylenediamine tetra-acetic acid (K2EDTA) anticoagulant and the remaining samples was left undisturbed at room temperature and later centrifuged at 3000rpm for 5minutes to obtain clear non- haemolysed plasma. The plasma was transferred into sterile labelled test tubes and assayed (in batches) for l-arginine and Nitric Oxide. Results: This study included children with a confirmed HbSS electrophoretic pattern aged 1-14 years with mean age 7.4500 ±0.50613 years, Presented to the sickle cell clinic unit of Federal Teaching Hospital Gombe, Gombe State. There was a statistically significant difference between the baseline and post L-arginine supplementation. The L-arginine and nitric oxide were significantly higher post supplementation compared to baseline levels among sickle cell disease subjects with vaso-occlusive crisis (p= 0.001and 0.01 respectively).